2019
DOI: 10.1093/digitalsh/fqz013
|View full text |Cite
|
Sign up to set email alerts
|

Withdrawn as Duplicate: Distant viewing: analyzing large visual corpora

Abstract: In this article we establish a methodological and theoretical framework for the study of large collections of visual materials. Our framework, distant viewing, is distinguished from other approaches by making explicit the interpretive nature of extracting semantic metadata from images. In other words, one must 'view' visual materials before studying them. We illustrate the need for the interpretive process of viewing by simultaneously drawing on theories of visual semiotics, photography, and computer vision. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…Drawing on a sample of archived websites between 1999 and 2014, for example, one research study found that in 1999 the percentage of text on an average webpage was only around 22%; peaking in 2005 at 32% and declining to around 25% by 2014 [4]. Elsewhere in the digital humanities, scholars are increasingly attuned to the "visual turn": the need to not only "distantly read" material, but to "distantly view" them as well [1]; examples include applications of neural networks to analyze image collections [13]. Our own previous work has attempted to provide scholars with image access into web archives by taking advantage of object detectors based on neural networks to create collages that portray a multitude of pre-defined objects [14].…”
Section: The Visual Turnmentioning
confidence: 99%
“…Drawing on a sample of archived websites between 1999 and 2014, for example, one research study found that in 1999 the percentage of text on an average webpage was only around 22%; peaking in 2005 at 32% and declining to around 25% by 2014 [4]. Elsewhere in the digital humanities, scholars are increasingly attuned to the "visual turn": the need to not only "distantly read" material, but to "distantly view" them as well [1]; examples include applications of neural networks to analyze image collections [13]. Our own previous work has attempted to provide scholars with image access into web archives by taking advantage of object detectors based on neural networks to create collages that portray a multitude of pre-defined objects [14].…”
Section: The Visual Turnmentioning
confidence: 99%
“…These contents are automatically and manually enriched with metadata at the level of a single shot or image. Automatic tagging of a/v content is a very sensitive and cherished topic among digital humanities scholars [Bermeitinger et al 2019], [Arnold and Tilton 2019]. In our case the automatic analysis, performed thanks to algorithms provided by Fraunhofer Institute (https://www.fraunhofer.de/en.html), delivers shot detection, camera movement, quality assessment and object detection for 66 different objects.…”
Section: I-media-citiesmentioning
confidence: 99%
“…Secondly, researchers can extract structured metadata from the mentioned textual object descriptions or make "intrinsic" object features explicit, by computationally extracting textual or visual features from the objects of a collection or from associated descriptions. As such, natural language processing [6,14] or computational image recognition and feature extraction techniques are frequently applied [3,[15][16][17].…”
Section: Related Workmentioning
confidence: 99%